2011
DOI: 10.1016/j.jcrs.2011.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative conversion from phacoemulsification to manual extracapsular cataract extraction

Abstract: Multiple 10-0 nylon sutures may be required to close the main wound and the side port. Seidel testing of the wounds and segment junctions is performed and additional sutures added to ensure a watertight seal. CASE REPORTThe importance of wound placement is demonstrated in a patient who had cataract surgery 4 years after keratolimbal allograft and tube-shunt surgery. Based on the tube location and efforts to avoid an inferiorly placed wound, the main wound was made adjacent to a keratolimbal allograft junction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…While study done by Mercieca Karl et al, reported common risk for intraoperative conversion in their centre was due to dense nucleus and capsulorhexis extension (5). There…”
Section: Introductionmentioning
confidence: 94%
“…While study done by Mercieca Karl et al, reported common risk for intraoperative conversion in their centre was due to dense nucleus and capsulorhexis extension (5). There…”
Section: Introductionmentioning
confidence: 94%